Comparative analysis of clinical and anthropometric parameters depending on risk factors for cardiovascular disease in overweight individuals (Bangladesh Journal of Medical Science, 2025)
Backgroud Overweight and obesity are recognized as one of the most significant medical and social problems of modern health care. According to who, more than 1.7 billion people worldwide are overweight or obese. Despite the fact that many risk factors for their development are studied. There are only isolated studies on the peculiarities of ethnic and climatic-geographical characters. In this regard, we have studied the risk factors for developing cardiovascular disease and, first of all, the most accessible clinical and anthropometric parameters for research: age, height, body weight, BMI, OT (body circumference), SAD, DAP, heart rate.The purpose of the study to analyze the clinical and anthropometric parameters depending on the risk factors for cardiovascular disease in overweight individuals.Materials and methods It was revealed that out of 1143 respondents, the number of deceased persons was 213, which was 18.6% of the total number of those studied. The type of study is observational prospective cohort. In 2015, respondents were surveyed using survey maps similar to 2003, developed using standardized methods.Results For 12 years (2003-2015) in the cohort we studied, there is a tendency to increase almost all clinical and anthropometric indicators (except growth, SAD, DAP), not only in people with hypertension, but also in those who do not have this disease.Conclusion High risks of fatal complications due to socio-demographic, clinical-metabolic and behavioral factors of polymorbidity of cardiovascular diseases and diabetes mellitus dictate the need to take these factors into account when implementing a disease management program at the primary health care level.Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 119-135